Modulating the Electronic Metal‐Support Interactions in Single‐Atom Pt1−CuO Catalyst for Boosting Acetone Oxidation. (13th May 2022) - Jiang, Zeyu; Tian, Mingjiao; Jing, Meizan; Chai, Shouning; Jian, Yanfei; Chen, Changwei; Douthwaite, Mark; Zheng, Lirong; Ma, Mudi; Song, Weiyu; Liu, Jian; Yu, Jiaguo; et al.
Abstract: The development of highly active single‐atom catalysts (SACs) and identifying their intrinsic active sites in oxidizing industrial hazardous hydrocarbons are challenging prospects. Tuning the electronic metal‐support interactions (EMSIs) is valid for modulating the catalytic performance of SACs. We propose that the modulation of the EMSIs in a Pt1 −CuO SAC significantly promotes the activity of the catalyst in acetone oxidation. The EMSIs promote charge redistribution through the unified Pt−O−Cu moieties, which modulates the d ‐band structure of atomic Pt sites, and strengthens the adsorption and activation of reactants. The positively charged Pt atoms are superior for activating acetone at low temperatures, and the stretched Cu−O bonds facilitate the activation of lattice oxygen atoms to participate in subsequent oxidation. We believe that this work will guide researchers to engineer efficient SACs for application in hydrocarbon oxidation reactions. Abstract : Modulation of the electronic metal‐support interactions (EMSI) of a single‐atom Pt1 −CuO catalyst promotes charge redistribution and electron back donation through unified Pt−O−Cu coordination bonds. Abundant positively charged Pt species and activated lattice oxygen atoms significantly enhance the catalytic performance of the material in acetone oxidation.